Case report on a very rare tumour of the urinary bladder: paraganglioma - Sengupta, Soumish; Dey, Ranjan K.; Sati, Abhishek; Ghosh, Kadambari (International Journal of Advances in Medicine, 2020)
Urinary bladder tumours are usually of three types; urothelial carcinoma, squamous cell carcinoma and adenocarcinoma. Urothelial carcinoma is the most common type of bladder carcinoma and accounts for almost 90% of all bladder carcinoma. It is also known as transitional cell carcinoma. Squamous cell carcinoma accounts for 4% and adenocarcinomas 2% of all bladder carcinomas. Urinary bladder paragangliomas are a very rare variety of bladder tumours which account for less than 0.06% of all bladder tumours. They are clusters of neuroendocrine cells associated with sympathetic and parasympathetic nervous system. Paragangliomas are tumours arising from these chromaffin cells. They are most commonly seen in the head and neck and account for about 70% of all paragangliomas. The same type of tumour when found in the adrenal glands is referred to as a pheochromocytoma. Paraganglioma is usually seen in the age group of 30 and 50 years. The tumour is often slow growing and benign. These tumours may be functional or non-functional. Functional ones present with symptoms of catecholamine excess, which include hypertension, palpitations, diaphoresis, headache, and post-micturition syncope.